3D-printed bioceramic scaffolds: From bone tissue engineering to tumor therapy. (1st October 2018) - Ma, Hongshi; Feng, Chun; Chang, Jiang; Wu, Chengtie
Graphical abstract: Abstract: Toward the aim of personalized treatment, three-dimensional (3D) printing technology has been widely used in bone tissue engineering owing to its advantage of a fast, precise, and controllable fabrication process. Conventional bioceramic scaffolds are mainly used for bone tissue engineering; however, there has been a significant change in the application of bioceramic scaffolds during the past several years. Therefore, this review focuses on 3D-printed bioceramic scaffolds with different compositions and hierarchical structures (macro, micro, and nano scales), and their effects on the mechanical, degradation, permeability, and biological properties. Further, this review highlights 3D-printed bioceramic scaffolds for applications extending from bone tissue regeneration to bone tumor therapy. This review emphasizes recent developments in functional 3D-printed bioceramic scaffolds with the ability to be used for both tumor therapy and bone tissue regeneration. Considering the challenges in bone tumor therapy, these functional bioceramic scaffolds have a great potential in repairing bone defects induced by surgery and kill the possibly residual tumor cells to achieve bone tumor therapy. Finally, a brief perspective regarding future directions in this field was also provided. The review not only gives a summary of the research developments in bioceramic science but also offers a new therapy strategy by extending multifunctions of traditional biomaterials toward a specific disease. Statement of significance: This review outlines the development tendency of 3D-printed bioceramic scaffolds for applications ranging from bone tissue regeneration to bone tumor therapy. Conventional bioceramic scaffolds are mainly used for bone tissue engineering; however, there has been a significant change in the application of bioceramic scaffolds during the past several years. Therefore, this review focuses on 3D-printed bioceramic scaffolds with different compositions and hierarchical structures (macro, micro, and nano scales), and their effects on the mechanical, degradation, permeability, and biological properties. Further, this review highlights 3D-printed bioceramic scaffolds for applications extending from bone tissue regeneration to bone tumor therapy. This review emphasizes recent developments in the functional 3D-printed bioceramic scaffolds with the ability to be used for both bone tumor therapy and bone tissue regeneration.